The End of Desire jrfm - James Lorenz (Journal for Religion, Film and Media, 2020)
This article explores the soteriological significance of desire in Сталкер (STALKER, Andrei Tarkovsky, RU 1979). At the heart of the film, deep within a paranormal and psychosomatic frontier called the Zone, is a space which signifies the end of all desire: the Room, a preternatural place of mystical power which is said to grant one's innermost wishes. The Zone and the Room become soteriological motifs. Tarkovsky's characters travel there motivated by a yearning for healing; a hope for salvation. This article explores this soteriological journey through the interplay of desire, hope, and belief, for this triad is the key conceptual scheme at work in the film. By analysing the film with a focus on this framework, several theological and soteriological concepts emerge which can be fruitfully explored. Above all, by focusing on the significance of this triad, a crucial aspect of Tarkovsky's religious thought comes to light: his understanding of the relationship between desire and love.